2004
DOI: 10.1196/annals.1316.037
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Noradrenergic and Dopaminergic Hyperactivity in the Development of Spontaneous Recurrence of Methamphetamine Psychosis and Susceptibility to Episode Recurrence

Abstract: The role of dopaminergic activity in susceptibility of methamphetamine (MAP) psychosis (flashbacks) to subsequent spontaneous recurrences was studied. Plasma monoamine metabolite levels were assayed in 23 flashbackers, of whom 10 experienced a single flashback, 8 exhibited subsequent flashbacks and 5 with the last episode; 18 nonflashbackers with a history of MAP psychosis; 9 subjects with persistent MAP psychosis; and 19 MAP user and 10 nonuser controls. All flashbackers had undergone frightening stressful ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Third, although our particular interest is in schizophrenia vulnerability, our personality measures of vulnerability are sensitive to risk for psychosis, including affective psychosis (Erlenmeyer-Kimling et al, 1993;Chapman et al, 1994). Increased DA release in response to stress may represent a risk factor for psychosis in general, rather than a risk factor for schizophrenia per se (Yui et al, 2004). Fourth, we did not find DA release to be correlated with cortisol levels, as was found in our previous study (Pruessner et al, 2004), nor did we observe differences in cortisol between groups, a result likely due to our low number of participants.…”
Section: Discussionmentioning
confidence: 99%
“…Third, although our particular interest is in schizophrenia vulnerability, our personality measures of vulnerability are sensitive to risk for psychosis, including affective psychosis (Erlenmeyer-Kimling et al, 1993;Chapman et al, 1994). Increased DA release in response to stress may represent a risk factor for psychosis in general, rather than a risk factor for schizophrenia per se (Yui et al, 2004). Fourth, we did not find DA release to be correlated with cortisol levels, as was found in our previous study (Pruessner et al, 2004), nor did we observe differences in cortisol between groups, a result likely due to our low number of participants.…”
Section: Discussionmentioning
confidence: 99%
“…In fact a variety of neurotransmitters are released under METH administration - namely, serotonin [66] glutamate [67-69] and acetylcholine [70, 71]. Among these, catecholamine neurons are considered as the main target since METH is a powerful DA and NE releaser [72, 73]. As a consequence, repetitive administration of METH leads to DA-and NE-dependent behavioural sensitization, which can be reproduced in different species.…”
Section: Molecular Effects Of Methamphetamine (Meth) On Catecholaminementioning
confidence: 99%
“…Accordingly, when evaluating the behavioural effects induced by a selective NET blocker in animals, this may reproduce the effects of amphetamines [116]. Lending further implications to these findings, some works have emphasized the role of increased NE release in producing sensitization following METH administration [73]. …”
Section: The Role Of Ne In Methamphetamine-induced Behavioural Changesmentioning
confidence: 99%
“…Recent findings have shown that chronic METH use alters synaptic plasticity in the brain, which may contribute to its adverse effects [35], include dependence, withdrawal syndrome and drug craving [9,17,34]. The METH use causes neurotoxicity in multiple neurotransmitter systems [13,18,41]. METH-induced alterations in dopamine levels in mesolimbic, nigrostriatal systems and prefrontal cortex involve in craving and rewarding effects of drug [16,28].…”
Section: Introductionmentioning
confidence: 99%